DYNAMICS OF WATER QUALITY PARAMETERS IN HYDROGRAPHIC CATCHMENTS WITH NATIVE FOREST AND PINE-PLANTED FORESTS - Cardoso, Kaíque Mesquita; Zakia, Maria José Brito; Rodrigues, Carolina Bozetti; Santos, Vanessa (Floresta, 2023)
The search for productive forests in line with an environmental balance is one of the tasks of good sustainable forest management, in which studies on water quality in production areas support the improvement of environmental conservation programs. Thus, this study aimed to determine the water quality in watersheds covered with native forest and pine-planted forests and to evaluate the effects of forest operations and precipitation on the dynamics of physical and chemical parameters of water. Data were collected for 10 years (2005 - 2015) in a fortnightly sampling frequency. The concentrations of nitrate, phosphorus, potassium, calcium, and magnesium were determined, as well as the physical parameters of total suspended solids, pH, turbidity, apparent color, and electrical conductivity in the water. Data were analyzed using the Mann-Whitney test at 5% probability and through multivariate analysis (principal component analysis and hierarchical cluster analysis). The water quality of both watersheds is similar and there is no significant difference between the physical parameters. While the watershed composed of native forest has a higher concentration of NO3-, K, and Mg in the water, the watershed with planted forests of Pinus has a higher concentration of Ca. There was a chemical and physical difference in the dynamics of the water concerning its precipitation. Mosaic forest management can influence the stability of quality parameters.